Pengembangan Kurikulim PAI Model Kurikulum 2013 - Deni Irawan; Ilham Putri Handayani (LP3M Sekolah Tinggi Agama Islam Nahdlatul Wathan SAMAWA SUMBAWA BESAR, 2022)
Abstract: The moral crisis that has occurred recently is because the previous curriculum, is still based on the transfer of knowledge or cognitive aspects, so a curriculum that is a able to overcome these problems is needed.The curriculum in question is the 2013 Islamic Education Model Curriculum, which is better known as Islamic religious education and manner. The purpose of this paper is to examine the development of Islamic Religious Education curriculum model 2013. This research uses literature study with data analysis technique used is content analysis technique. The results of this study indicate that the development of Islamic religious education curriculum and character examines 5 components including: 1)the purpose of this Islamic religious education curriculum and manner emphasizes the formation of students who have noble character and are religiously obedient. 2) the material in the curriculum develops three realms, namely the domains of attitudes, knowledge and skills. 3) Strategy/methods should use a scientific curriculum approach. 4) the curriculum organization developed is an integrated curriculum model. 5) evaluation activities cover three domains.Keywords: Curriculum Development, Islamic Religious Education and Manner, 2013 Curriculum Model